Effect of metformin treatment in patients with type 2 diabetes with respect to glyoxalase 1 activity in atherosclerotic lesions - Peters, Andreas; Wortmann, Markus; Fleming, Thomas; Nawroth, Peter Paul; Bruckner, Thomas; Böckler, Dittmar; Hakimi, Maani (Vasa, 2019)
. Background: The enzyme glyoxalase1 (GLO1) is the main opponent in the degradation of the reactive metabolite methylglyoxal (MG), which by glycation of macromolecules is involved in atherogenesis. Reduced GLO1-activity in atherosclerotic tissue is known to be associated with diabetes. It has been shown that treatment of patients with type 2 diabetes with metformin leads to increased GLO1-activity in peripheral-blood-cells. The aim of this study was to evaluate whether metformin treatment increases GLO1-activity in atherosclerotic lesions of patients with type 2 diabetes. Patients and methods: Patients with type 2 diabetes and carotid artery disease were included into the study prospectively. Type of diabetes-medication was documented upon admission along with demographic and clinical history. Using shock frozen endarterectomy-derived carotid artery plaques, GLO1-activity as well as protein expression was measured by a spectophotometric assay and western-blotting respectively. Results: 33 patients (76 % male, mean age 71 years) were included into the study and were divided according to treatment with metformin or not (15 vs. 18 patients). GLO1-activity was increased by the factor 1.36 when treated with metformin - however, not significantly (0.86 vs. 0.63 U/mg, p = 0.056). Normalisation of GLO1-activity onto GLO1-expression level lead to a significant increase by more than twofold (8.48 vs. 3.85, p = 0.044) while GLO1-protein levels did not differ significantly. GLO1-activity correlated positively with increasing HbA1c, especially under metformin treatment. Conclusions: Treatment with metformin in patients with type 2 diabetes is associated with enhanced GLO1-activity in atherosclerotic lesions. Regarding the macro- and microvascular complications in these patients further studies are needed to gain more insight into the effect of metformin on the GLO/MG system.
Onlineveröffentlichung: November 13, 2018
Gesehen am 13.06.2019